Testing overconfidence bias in Pakistani stock market - Lubna Zia; Muzammal Ilyas Sindhu; Shujahat Haider Hashmi (Cogent Economics & Finance, 2017)
Excessive trading phenomenon is contrary to the concept of traditional finance that is based on the rational expectation theorem and efficient market hypothesis. Therefore, this study is aimed at exploring the existence of overconfidence behavior in the stock market. The market-wide panel VAR model is used to investigate the lead-lag relationship between stock returns and turnover. Our results suggest that investors are overconfident in Pakistani stock market because turnover depends directly upon stock returns. The findings have important implications for investors and brokers for developing appropriate trading strategy.
Keywords: C01; E44; G15; 330; overconfidence; turnover; volatility; panel VAR